Spectral analysis and low-frequency multipath mitigation for kinematic applications - Souza, E. M. de [UNESP]; Monico, J. F. G. [UNESP]; Polezel, W. G. C. [UNESP]; Pagamisse, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Low-frequency multipath is still one of the major challenges for high precision GPS relative positioning. In kinematic applications, mainly, due to geometry changes, the low-frequency multipath is difficult to be removed or modeled. Spectral analysis has a powerful technique to analyze this kind of non-stationary signals: the wavelet transform. However, some processes and specific ways of processing are necessary to work together in order to detect and efficiently mitigate low-frequency multipath. In this paper, these processes are discussed. Some experiments were carried out in a kinematic mode with a controlled and known vehicle movement. The data were collected in the presence of a reflector surface placed close to the vehicle to cause, mainly, low-frequency multipath. From theanalyses realized, the results in terms of double difference residuals and statistical tests showed that the proposed methodology is very efficient to detect and mitigate low-frequency multipath effects. © 2008 IEEE.
Keywords: Feature extraction; Kinematics; Navigation; Spectrum analysis; Spectrum analyzers; Wavelet transforms; Double differences; Geometry changes; High precisions; Kinematic applications; Multi-path effects; Multipath; Multipath mitigations; Reflector surfaces; Spectral analyses; Stationary signals; Vehicle movements; Statistical tests